Maternal obesity phenotype, metabolic dysfunction, and preterm birth: a prospective birth cohort study - Chen, Jiayi; Miao, Yecheng; Li, Qingxiu; Zhang, Qian; Sun, Bin; Wu, Zhengqin; Liu, Wenjuan; Liu, Junwei; Shi, Huimin; Gao, Haiyan; Li, Wei; Zhu, Yibing; et al. (Frontiers in Nutrition, 2025)
IntroductionThe purpose of this research was to examine the relationship between metabolic obesity phenotypes and preterm birth (PTB) as well as the impact of obesity and metabolic abnormalities on PTB.MethodsA total of 20,259 pregnant singleton women participated in prospective birth cohort research conducted in China. Obesity metabolic phenotypes were categorized using pre-pregnancy body mass index (BMI) and metabolic state. Any delivery before 37 full weeks of gestation, as determined by the best obstetric estimate available, was considered PTB.ResultsAs the number of metabolically unfavorable components grows, so does the risk of developing PTB. Compared to women with a metabolically healthy normal weight, those who are normal weight and overweight (including obese) with metabolically unwell had an increased chance of having PTB (adjusted OR: 1.33 and 1.62, respectively). Additionally, additive interaction analysis revealed a significant interaction between overweight and metabolic unhealthiness for PTB risk (RERI = 0.41, AP = 0.24, SI = 2.22). People who are overweight and metabolically unwell have a 0.41 relative excess risk (which accounts for 24%) of PTB, and their combined risk is 2.22 times higher than that of those who are exposed to either risk alone.ConclusionPTB risks are increased by metabolic abnormalities and overweight (including obese), and there are notable interaction effects between metabolic abnormalities and overweight (including obese) and PTB.